Pengenalan Penggunaan Google Form Untuk Survei Kepada Warga Darma Bakti, Cengkareng, Jakarta Barat - Firdaus, Mohamad; Bakti, Indra (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
This research aims to introduce and implement the use of google form as a survei tool to collect data from residents of Darma Bakti, Cengkareng, West Jakarta. The research method involves developing a survei form using the google form platform that can be accessed online. The research also explored the effectiveness of google form in collecting data on various aspects of Darma Bakti residents' lives and needs. The research process involved introducing the concept and functionality of google form to respondents, as well as brief training to increase participation in the survei. The data collected included demographic information, preferences, and feedback related to services and facilities obtained from Darma Bakti residents. Data analysis involved the use of automated analysis features provided by google form, as well as manual interpretation to gain deeper insights. The results of this study are expected to provide a better view of the use of google form as an effective and efficient tool for citizen surveis, as well as provide valuable input for the improvement of services and facilities in the Darma Bakti neighborhood, Cengkareng, West Jakarta. This research also contributes to the literature related to the use of online survei technology, especially in the context of local communities.